Minnie & Moo : hooves of fire - Cazet, Denys (Creston Books, LLC, 2014)
To raise money for a down payment on a new tractor for Mr. and Mrs. Farmer, cow friends Minnie and Moo organize the First Annual Hoot, Holler, and Moo Talent Festival.